Dexmedetomidine Improves Learning Functions in Male Rats Modeling Cognitive Impairment by Modulating the BDNF/TrkB/CREB Signaling Pathway - Sinan Saral; Tolga Mercantepe; Atilla Topçu; Ali Koray Kaya; Aykut Öztürk (Life)
Dexmedetomidine (DEX) is a selective alpha-2 adrenergic receptor agonist with sedative and anxiolytic properties. Increasing evidence reports that DEX has a neuroprotective effect. In this study, we investigated the potential effects of DEX on learning and memory functions in rats with experimental cognitive impairment. In the study, 21 adult male rats were used. The rats were divided into three groups, namely control, Scopolamine (SCOP) and SCOP + DEX. Cognitive impairment was induced with 1 mg/kg SCOP daily for 21 days. DEX was administered at a dose of 10 µg/kg between days 14 and 21 of the experiment. Following the injections, a spatial memory test was performed with a Morris Water Maze (MWM). At the end of the experiment, the hippocampus was dissected. The brain-derived neurotrophic factor (BDNF), acetylcholine (ACh) and acetylcholinesterase (AChE) levels were determined by ELISA. The tropomyosin receptor kinase B (TrkB) and Cyclic AMP-Response Element-Binding Protein (CREB) levels were measured by immunohistochemistry. DEX treatment improved the learning performance of rats compared to SCOP for 5 days. However, it did not significantly change memory performance. DEX increased the BDNF and ACh levels in the hippocampus while decreasing the AChE levels. Similarly, DEX treatment significantly increased CREB phosphorylation. No significant difference was observed between the TrkB receptor levels of the groups. This study demonstrated that the role of DEX in reducing SCOP-induced cognitive impairment is partially mediated by the increase in BDNF/TrkB/CREB signaling pathway activity.